RESPON MASYARAKAT TERHADAP USAHA EKONOMI DESA SIMPAN PINJAM (UED-SP) DESA PULAU BUSUK JAYA KECAMATAN INUMAN KABUPATEN KUANTAN SINGINGI - Desrita "; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study entitled " Community Response Against Economic Enterprises Village Savings and Loans ( UED - SP )  Island Village Foul Jaya Regency Districts Inuman District Kuantan Singingi”. Researchers are interested to raise this friend because of the problems that exist in society about how public opinion about the program UED – SP. Data analysis was conducted to address the existing problems in this study is are analyzed quantitatively that provide a picture of the actual state of society, concerns the public response to government programs ( UED - SP ) were analyzed based on the theories in this study. Here's the problem : (1) Who are the recipients of loans UED - SP in the village of Rot Jaya Regency Districts Inuman District Kuantan Singingi. (2) For any loan funds used by the UED - SP Desa Jaya District Rotten Island Regency Districts Inuman District Kuantan Singingi. Data collection techniques in this research is observation , interview and questionnaire. As for the method of taking the sample population conducted by purposive random sampling technique , ie by 50 % in each character by counting the number of samples. While the population of the entire population of 122 people nasaba, nasaba pay between 54 and 68 people smoothly nasaba pay jammed.    Keywords : Response , society , UED - SP